(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Suspension bushings play an important role in reducing vibrations, minimizing noise, absorbing road irregularities, and controlling joint movements. Polyurethane bushings, in particular, contribute to improved vehicle handling, exhibiting lower moments of inertia and greater strength under increased loads. However, this enhancement in performance may come at the expense of reduced ride comfort. This paper presents the results of a study on the mechanical characteristics of polyurethane material and the stiffness of bushings made from the same material, specifically in the context of the MacPherson front independent suspension. To achieve this, mechanical tension tests were conducted on polyurethane specimens, obtaining stress-strain curves. Additionally, a three-dimensional geometric model of the polyurethane bushing was created using the SolidWorks software. The paper presents the results of bushing stiffness obtained through nonlinear Finite Element Analysis (FEA). Experimental determination of radial stiffness was also performed, and the results were compared for validation.